2004
DOI: 10.1246/cl.2004.1608
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Nanocrystals as Fluorescent Sensors for Hg2+ Ions

Abstract: CdTe nanocrystals as fluorescent sensors for Hg2+ ions were synthesized. These nanocrystals were highly sensitive for Hg2+ ions and the selectivity was found to be Hg2+ > Cu2+ > other representative heavy metal ions. Moreover, they bear the following merits. First, they are easily synthesized; second, they have a narrow, tunable, symmetric emission spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…The methods currently used for the determination of Hg 2? ions include atomic absorption spectrometry (Butler et al 2006), inductively coupled plasma-mass spectrometry (Li et al 2006), selective cold vapor atomic fluorescence spectrometry (Leermakers et al 2005), organic fluorophores/chromophores (Zhu et al 2006;Guo et al 2011;El-Safty et al 2008;Coronado et al 2005), semiconductor nanocrystals (Chen et al 2004;Page et al 2011), cyclic voltammetry (Nolan and Kounaves 1999;Kim et al 1998), etc., based techniques. However, most of these conventional techniques are invariably complicated, time-consuming, expensive as well as inconvenient for point-of-use applications.…”
Section: Introductionmentioning
confidence: 99%
“…The methods currently used for the determination of Hg 2? ions include atomic absorption spectrometry (Butler et al 2006), inductively coupled plasma-mass spectrometry (Li et al 2006), selective cold vapor atomic fluorescence spectrometry (Leermakers et al 2005), organic fluorophores/chromophores (Zhu et al 2006;Guo et al 2011;El-Safty et al 2008;Coronado et al 2005), semiconductor nanocrystals (Chen et al 2004;Page et al 2011), cyclic voltammetry (Nolan and Kounaves 1999;Kim et al 1998), etc., based techniques. However, most of these conventional techniques are invariably complicated, time-consuming, expensive as well as inconvenient for point-of-use applications.…”
Section: Introductionmentioning
confidence: 99%
“…Their excellent PL properties endow them with considerable applications in biological labeling, cellular effectors and reporters [11]. Simultaneously, many researchers make efforts to use QDs for detection of some metal ions [1,2,8,[12][13][14][15][16][17][18][19][20], small molecules [21][22][23][24][25], and temperature [26]. For metal ions, Cu (II) and Ag (I) are widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Konishi and Hiratani [12] found that the PL intensity of Cd 10 S 16 molecular cluster can be effectively increased by Cu + in water. Besides the above activation effect, some heavy metal ions, such as Cu 2+ and Hg 2+ , effectively quench PL of QDs [13][14][15][16][17][18][19]. Interestingly, most reports demonstrated that Ag + could quench PL of cadmium chalcogenide (CdS, CdSe or CdTe) nanoparticles [14,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%